Answer

Verified

455.1k+ views

**Hint:**First we’ll find the sum of the 5 numbers using the average formula, after getting the difference of that sum to the fifth number we’ll have the sum of the first four numbers. After getting the sum of the first four numbers we can easily find the average of those 4 numbers.

**Complete step by step answer:**

Given data: Average of 5 numbers=10

Fifth number=6

Now, ${\text{average = }}\dfrac{{{\text{sum of all elements}}}}{{{\text{number of elements}}}}$

According to the given data, we can conclude that,

Average of 5 numbers${\text{ = }}\dfrac{{{\text{sum of 5 numbers}}}}{{\text{5}}}$

$

\Rightarrow {\text{10 = }}\dfrac{{{\text{sum of 5 numbers}}}}{{\text{5}}} \\

\Rightarrow {\text{sum of 5 numbers = 10(5)}} \\

{\text{ = 50}} \\

$

Therefore the sum of 5 numbers=50

But the fifth number=6

Now, we can say that the sum of the first 4 numbers will be equal to the difference of the sum of 5 numbers and the fifth number i.e.

the sum of the first four numbers=sum of five numbers-fifth number

\[

{\text{the sum of the first four numbers = 50 - 6}} \\

{\text{ = 44}} \\

\]

Therefore, according to the formula of average, the average of the first four numbers will be

\[

\therefore {\text{average of the first four numbers = }}\dfrac{{{\text{sum of first four numbers}}}}{{\text{4}}} \\

{\text{ = }}\dfrac{{{\text{44}}}}{{\text{4}}} \\

{\text{ = 11}} \\

\]

**Option (C) 11 is the correct option**

**Note:**An alternative way to find the solution can be,

Since it is well known that,

\[

{\text{average of the first four numbers = }}\dfrac{{{\text{sum of first four numbers}}}}{{\text{4}}} \\

\Rightarrow {\text{sum of first four numbers = 4}}\left( {{\text{average of the first four numbers}}} \right) \\

\]

And,

$

{\text{Average of 5 numbers = }}\dfrac{{{\text{sum of 5 numbers}}}}{{\text{5}}} \\

\Rightarrow {\text{10 = }}\dfrac{{{\text{sum of first 4 numbers + fifth number}}}}{{\text{5}}} \\

\Rightarrow {\text{10 = }}\dfrac{{{\text{sum of first 4 numbers + 6}}}}{{\text{5}}} \\

$

From the above equations, we conclude that

$

{\text{10 = }}\dfrac{{{\text{4}}\left( {{\text{average of the first four numbers}}} \right){\text{ + 6}}}}{{\text{5}}} \\

\Rightarrow {\text{4}}\left( {{\text{average of the first four numbers}}} \right){\text{ + 6 = 5(10)}} \\

\Rightarrow {\text{4}}\left( {{\text{average of the first four numbers}}} \right){\text{ = 50 - 6}} \\

\Rightarrow {\text{average of the first four numbers = }}\dfrac{{{\text{44}}}}{{\text{4}}} \\

{\text{ = 11}} \\

$

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Why is there a time difference of about 5 hours between class 10 social science CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Draw a labelled sketch of the human eye class 12 physics CBSE